Business Sustainability: Analysis of Corporate Social Responsibility - Saritha S R; Bhaskar A; Avni KC; Charul S Kumar; Vaishakh Prakash; Dheeraj S Chordia; Dhruv Mehta (International Journal of Engineering and Management Research, 2023)
Since businesses are increasingly recognizing the significance of addressing environmental and social issues, the idea of sustainability in business has received a lot of attention in recent years. Companies' voluntary efforts to reduce their negative effects on society and the environment are referred to as "corporate social responsibility" (CSR), and it is a crucial component of business sustainability. This paper examines corporate social responsibility (CSR) in the context of business sustainability, highlighting its advantages, drawbacks, and contribution to sustainability promotion. The paper also discusses the difficulties that businesses face when putting CSR initiatives into action, such as measuring their impact, responding to the demands of stakeholders, and striking a balance between social and environmental objectives and financial considerations. The paper concludes by stressing the significance of corporate social responsibility (CSR) in promoting business sustainability and urging businesses to adopt more environmentally friendly business practices.